Pyrazole alkaloids from watermelon (Citrullus lanatus) seeds. (June 2015) - Kikuchi, Takashi; Ikedaya, Aoi; Toda, Akiko; Ikushima, Kenji; Yamakawa, Takahiro; Okada, Rina; Yamada, Takeshi; Tanaka, Reiko
Graphical abstract: Highlights: Three new compounds (1 –3 ) were isolated from an extract of watermelon seeds. 1 and 2 were compounds with pyrrole and pyrazole rings in a molecule. 1 –3 were evaluated for melanogenesis inhibitory activities. 1 exhibited modest inhibitory activity (inferior to arbutin) without cytotoxicity. Abstract: Three new compounds, i.e. 1-[2-(5-hydroxymethyl-1 H -pyrrole-2-carbaldehyde-1-yl)ethyl]-1 H -pyrazole (1 ), 1-({[5-(α-d -galactopyranosyloxy)methyl]-1 H -pyrrole-2-carbaldehyde-1-yl}-ethyl)-1 H -pyrazole (2 ), and (4-hydroxyphenyl)methanol 4-[β-d -apiofuranosyl(1→2)- O -β-d -glucopyranoside] (3 ), were isolated from an extract of watermelon seeds. Compounds 1 and 2 were pyrazole-alkaloids with a pyrrole ring. This is the first study to show compounds with pyrrole and pyrazole rings in a molecule isolated from natural products. In the evaluation for melanogenesis inhibitory, compound 1 exhibited modest inhibitory activity on melanogenesis without cytotoxicity. Meanwhile compound 2 showed some inhibitory activity accompanied by some cytotoxicity.